Dihydroxyacetone valorization with high atom efficiency via controlling radical oxidation pathways over natural mineral-inspired catalyst - Jinling Wang (Nature Portfolio, 2021)
Radicals-mediated Fenton chemistry has the potential for biomass valorization. Here, inspired from the natural goethite mineral, the authors develop a MnO2/goethite catalyst showing excellent yields of glycolic acid and formic acid from dihydroxyacetone, an important biomass-based platform molecule.